2-(Tritylsulfanyl)ethyl 3-iodobenzoate - Zhu, Xin; Ng, Seik Weng (International Union of Crystallography, 2011)
The triphenyl-methyl group in the title compound, C 28H 23IO 2S, has the methine carbon slightly flattened out [∑C phen-yl- C-C phenyl = 332.8 (6) °]. The -C-O-C-C-S- chain connecting the triphenyl-methyl group and the aromatic ring adopts an extended zigzag conformation, these five atoms being approximately co-planar (r.m.s. deviation 0.260 Å).